ANALISA PROSES PENJUALAN DAN PENGIRIMAN BARANG DI PT. FENSEM TOMODACHI INDONESIA - Tri Winarto; Muammar Zaenuddin Rabbani (POLITEKNIK LP3I JAKARTA, 2024)
This study aims to analyze the sales and delivery process of goods at PT Fensem Tomodachi Indonesia. The technique of collecting data through literature studies, field studies and observation is to directly observe the object being examined. The obstacles that occur in the analysis of the sales dan delivery process at PT Fensem Tomodachi Indonesia, the absence of a warehouse to accommodate product,there are often delays in sending goods, as a result the sales and delivery process is not optimal. The temporary solution is to submit a request for cooperation with the delivery service to create a display rack to store product samples that are in high demand,implementinga 14 day payment system after the goods are received. Keywords : Analysist ,Sales, Delivery